1999
DOI: 10.1002/(sici)1098-2744(199906)25:2<122::aid-mc7>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of susceptibility to diverse skin tumor promoters by activation of the insulin-like growth factor-1 receptor in the epidermis of transgenic mice

Abstract: Insulin-like growth factor-1 (IGF-1) and its receptor are believed to play an important role in mitogenesis and neoplastic transformation. The purpose of this study was to further examine the role of IGF-1 during tumor promotion in mouse skin. HK1.IGF1 transgenic mice, which overexpress IGF-1 in epidermis via the human keratin 1 promoter, were previously shown to be hypersensitive to skin tumor promotion by 12-O-tetradecanoylphorbol-13-acetate (TPA). We examined these mice for their sensitivity to diverse clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…5 and 6, topical treatment of both wild-type mice and LID mice with either 3.4 or 6.8 nmol of TPA led to rapid activation (i.e., phosphorylation) of the EGFR, IGF-IR/IR, IRS-1, Akt, mTOR, and downstream effectors of mTOR (e.g., p70S6K, p-eIF4B, p-4E-BP1, and p-S6-ribosomal protein). These data are consistent with previously published data from our laboratory (16,17,24,25). Notably, the level of activation as assessed by phosphorylation of all signaling molecules examined was reduced in LID mice following TPA treatment compared with wild-type littermates (Figs.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…5 and 6, topical treatment of both wild-type mice and LID mice with either 3.4 or 6.8 nmol of TPA led to rapid activation (i.e., phosphorylation) of the EGFR, IGF-IR/IR, IRS-1, Akt, mTOR, and downstream effectors of mTOR (e.g., p70S6K, p-eIF4B, p-4E-BP1, and p-S6-ribosomal protein). These data are consistent with previously published data from our laboratory (16,17,24,25). Notably, the level of activation as assessed by phosphorylation of all signaling molecules examined was reduced in LID mice following TPA treatment compared with wild-type littermates (Figs.…”
Section: Resultssupporting
confidence: 93%
“…The reduction in epidermal proliferation observed in LID mice following TPA treatment may explain, in part, the significant inhibition of skin tumorigenesis seen in LID mice. As noted in the Introduction, previous work from our laboratory using transgenic mice in which IGF-I expression was elevated at the tissue level through targeted overexpression in skin keratinocytes showed that these mice have an increased susceptibility to two-stage skin carcinogenesis (10,25,26). The current results clearly show that levels of circulating IGF-I can also directly affect the susceptibility to skin tumor promotion and two-stage skin carcinogenesis.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…10,11 These effects have been extensively investigated in a variety of solid tumors including breast, prostate, lung, ovary, skin, and soft tissue cancers. [12][13][14][15][16] It is not surprising, therefore, that inhibitors of IGF-IR are currently being evaluated in several clinical trials enrolling patients with some of the most aggressive and resistant types of solid cancers, and some of these inhibitors have shown promising effects. 17,18 It is of note that, in contrast to the widely studied solid tumors, not so many studies have been performed to systematically explore a role of IGF-IR in hematologic neoplasms.…”
Section: Introductionmentioning
confidence: 99%